2013
DOI: 10.1515/dema-2013-0439
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional matrix transformation and A-statistical fuzzy Korovkin type approximation

Abstract: Abstract. In this paper, we prove a fuzzy Korovkin-type approximation theorem for fuzzy positive linear operators by using A-statistical convergence for four-dimensional summability matrices. Also, we obtain rates of A-statistical convergence of a double sequence of fuzzy positive linear operators for four-dimensional summability matrices. IntroductionAnastassiou . In this paper, we prove a fuzzy Korovkin-type approximation theorem for fuzzy positive linear operators by using A-statistical convergence for four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Then using the similar technique as in the proof of Theorem 4, one can also get the following result. If the ideal I in Theorem 5 is replaced by I 0 ; we immediately get the following result proved in [4].…”
Section: Smentioning
confidence: 82%
See 1 more Smart Citation
“…Then using the similar technique as in the proof of Theorem 4, one can also get the following result. If the ideal I in Theorem 5 is replaced by I 0 ; we immediately get the following result proved in [4].…”
Section: Smentioning
confidence: 82%
“…Later, using different summability methods, some Korovkin type theorems have been obtained by many authors in several ways. For instance, see [4], [6][7][8][9], [10]. In recent years, the studies on double sequences has a rapid growth.…”
Section: Introductionmentioning
confidence: 99%
“…Let f ∈ C * (R 2 ) and (x, y) ∈ [−π, π] × [−π, π]. Then in view of the proof of Theorem 9 in [6] we have…”
Section: Resultsmentioning
confidence: 99%
“…Besides, in connection with sequence transformations, weighted mean methods and power series methods of summability have been applied to Korovkin type theorems to recover the convergence of operators for which classical Korovkin theorems fail to work [5,8,11,12,14,15]. Furthermore, there are studies dealing with Korovkin type theorems via weighted mean summability methods for continuous functions of two variables [1,4,6,7]. In this paper, we prove a Korovkin type approximation theorem for 2π-periodic and real valued continuous functions on R 2 by using power series methods of summability and also give an approximation theorem by using modulus of continuity.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical convergence in approximation theory was first used by Gadjiev and Orhan [3] to prove the Korovkin-type approximation theorem [4]. The studies and related results can be found in [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%